Meningkatkan Hasil Belajar Peserta Didik Melalui Metode Problem Based Learning pada Peserta Didik Kelas 2 Fase A SD Mardi Waluya Cibinong - Franciska Triningsih; Hartutik Hartutik (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
At Elementary School Mardi Waluya Cibinong, it was found that the critical thinking ability and learning achievement targets of Catholic Religious Education especially in grade 2 were not optimal. This could be due to the use of less varied learning methods and the less optimal implementation of strategies that encourage active student participation. This research aims to improve the character dimension of critical thinking and student achievement targets by applying the Problem-Based Learning method in phase A of especially in grade 2. This classroom action research was conducted in two cycles with materials on the safety of God’s work through Kain and Habel, with each cycle consisting of four stages: planning, implementation, evaluation, and reflection. The research subject is students from Elementary school Mardi Waluya Cibinong with a total of 34 peoples. The results of the research show that the use of the PBL learning model can increase the character dimension of critical thinking in the Pancasila student profile (P3) from 70% to 84%. There was also an increase in student achievement outcomes, with mastery increasing from 20% to 68%, proficiency from 50% to 32%, and a decrease in appropriateness from 18% to 0%, which then increased to 12%. This indicates a significant decrease in the critical thinking dimension of the Pancasila students profile, which overall improves the critical thinking process and students achievement in grade 2 phase A. Recommendation: Teachers can focus on one dimension of P3 in the character development process by applying problem-solving learning methods.